Pediatric Lens Diseases - Liu, Yizhi (Springer Singapore : Imprint: Springer, 2017)
This book focuses on disorders of the lens, which are a major cause of blindness in children. During development, children's eyes have unique physiological and structural characteristics, such as an immature blood-aqueous barrier, which presents considerable challenges for ophthalmologists involved in the diagnosis and treatment of pediatric lens disorders. Throughout the book, the pathology, examination, anesthesia, surgical treatment and nursing care of pediatric lens disorders are discussed in detail. It not only presents diverse pictures and images from clinical practice, it also includes the latest findings in the field. It will be of interest to ophthalmologists and paediatricians looking to improve the diagnosis and treatment of pediatric lens disorders and provide a valuable reference resource for all those involved in ophthalmic clinical practice, teaching and research. Yizhi Liu is a professor and director of Zhongshan Ophthalmic Center, Sun Yat-sen University, China and he is also the director of State Key Laboratory of Ophthalmology at Zhongshan Ophthalmic Center, China.